PENGARUH KUALITAS LAPORAN KEUANGAN TERHADAP EFISIENSI INVESTASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Bahy, Novita Melisa (Politeknik Negeri Lhokseumawe, 2024)
Abstract : This study aims to analyze and determine the Effect of Financial Statement Quality on Investment Efficiency. The population in this study is Energy Sector companies on the Indonesia Stock Exchange for the period 2020-2023. Sampling in the study used purposive sampling method. The total number of samples in this study is 92 companies in the Oil, gas and coal subsector. The research method used is secondary research. The dependent variable in the study is investment efficiency. The independent variable in this study is the quality of financial reporting. The data analysis technique in this study uses simple linear analysis with model feasibility test (F test) and partial regression test (t test). The data processing process is carried out using the Statistical Package for Social Science (SPSS) program. The results showed that the Quality of Financial Statements has a significant positive influence on investment efficiency on the IDX with a significant value of 0.000 and contributes to investment efficiency by 12.8%. Keywords: Financial Report Quality,Investment Efficiency